Friedrich Nietzsche e a educação : crítica à metafísica e a formação do homem superior - Martello, Dionei José (2015)
This thesis aims understand the role of training and from the educator at the thought of Nietzsche, with regard to the need for host of the cultural horizon and civilizatory by the subject, and at the same time, the not rebuttable importance of taking into account the peculiarities and idiosyncrasies, when crucial concern to individuals above the common order. To get to the realization of this objective analyzes, firstly, some basic elements that make up your critical philosophy. That is, how he conceived the moral of the European nineteenth century society, which vector elements were responsible for the genesis of the values revered by his contemporaries and what new values should emerge and supplant the old. In this same line of thought investigates how Nietzsche conceives of human reason and how, to the German philosopher, the human being should behave to accept and winning the absence of transcendent sense of the world (The nihilism), and use their cognitive abilities in the most appropriate and efficient way possible (within what humanly viable and rationally feasible). After these opening remarks ascertains which, so to speak, "role" assigned to education, the formation and the role of master of anthropological and philosophical concepts woven by Nietzsche, but also how the old educational structures are an obstacle to realize them. In this sense, will be vitally important to understand how rationalism, industrialization and technical progress, products and side effects arising with the Enlightenment, led to a strong decline in the spirit and in European culture, debasing man to a cog in the wheel of the industrial-capitalist system. Through this analysis, Nietzsche directs the sting of his criticism of the State, as institutional power advocate of liberalism and therefore responsible for maintaining the same. After these considerations, the work portrays how science, philosophy and art should work, within a new training context, so that men with higher instincts to explore their potential and contribute to the advancement of human civilization. In other words, how such systems could make use of the theoretical legacy of generations to form the subject without, thereby, undo what he has in the wild.